2009
DOI: 10.1038/eye.2009.103
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of ultrasound biomicroscopy and anterior segment optical coherence tomography for evaluation of anterior chamber dimensions in European eyes with primary angle closure

Abstract: Purpose To compare the accuracy in measurement of the anterior chamber (AC) angle by anterior segment optical coherence tomography (AS-OCT) and ultrasound biomicroscopy (UBM) in European patients with suspected primary angle closure (PACS), primary angle closure (PAC), or primary angleclosure glaucoma (PACG). Design Cross-sectional study. Methods In all, 55 eyes of 33 consecutive patients presenting with PACS, PAC, or PACG were examined with AS-OCT, followed by UBM. The trabecular-iris angle (TIA) was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 27 publications
5
19
1
3
Order By: Relevance
“…Mansouri ve ark. 'n›n yapt›klar› çal›flmada ise; UBM ve ÖS-OKT ile yap›lan ön kamara ölçümleri aras›nda önemli korelasyon oldu¤u ancak zay›f kararl›l›k gösterdi¤i, ön kamara aç›s›n›n niceliksel ölçümünde ÖS-OKT'nin UBM'nin yerini alamayaca¤›na inand›klar›n› belirtmifllerdir (10).…”
Section: Tart›flmaunclassified
“…Mansouri ve ark. 'n›n yapt›klar› çal›flmada ise; UBM ve ÖS-OKT ile yap›lan ön kamara ölçümleri aras›nda önemli korelasyon oldu¤u ancak zay›f kararl›l›k gösterdi¤i, ön kamara aç›s›n›n niceliksel ölçümünde ÖS-OKT'nin UBM'nin yerini alamayaca¤›na inand›klar›n› belirtmifllerdir (10).…”
Section: Tart›flmaunclassified
“…For some Authors there's poor agreement between AS OCT and UBM: the first giving higher measurements than the second, but the reasons still remain unclear. It has been hypothesized that it can be due to the different calibration, to illumination condition, or to pressure of the eyecup [68,96].…”
Section: Anterior Segment Optical Coherence Tomography (As-oct)mentioning
confidence: 99%
“…Determination of angle parameters using semiautomated software leads to variability in measurements and this is largely due to the need of manual identification of the sclera spur [96]. Using Visante OCT the scleral spur individuation is possible in approximately 70% of anterior segment images [97].…”
Section: Anterior Segment Optical Coherence Tomography (As-oct)mentioning
confidence: 99%
“…The Pentacam HR (Oculus, Wetzlar, Germany) and the Galilei G4 (Ziemer, Switzerland) are two clinical tomographers that are both based on Scheimpflug cameras. Beside corneal parameters, these devices also have the ability to measure the ACD, ACA, PD, and ACA, and they (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) or WTW distance (20)(21)(22) . However, to our knowledge, a side by side comparative study has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the WTW distance is useful in determining the optimum IOL size, and the PD is essential in determining the optical zone where the laser pattern has to be applied. Also, an anterior chamber angle (ACA) evaluation is essential to establish the risk of angle disclosure (1) . Recent technological advances have allowed the ACD, WTW, PD, and ACA measurements to be quantified with the following noninvasive techniques: Scheimflug photography (Pentacam-Galilei), scanning slit topography (Orbscan/OrbscanII), and partial (IOLMaster) and low coherence interferometry (Visante-optical coherence interferometry and Lenstar).…”
Section: Introductionmentioning
confidence: 99%